(untitled) (Stavební obzor - Civil Engineering Journal, 2015)
Water yield from catchments with a high evidence of fog or low clouds could be increased by the canopy fog drip. However, in areas with the acid atmospheric deposition, this process can lead to the decline of water quality. The aim of this study is to analyze fog related processes in headwater catchments of the Jizera Mountains (the Czech Republic) with special attention to water quality and the drinking water treatment. In two years (2011-2012), the fog drip was observed by twelve passive fog collectors at transect of the Jizerka experimental catchment. Methods of space interpolation and extrapolation (ArcGis 10.2) were applied to approximate the areal atmospheric deposition of fog water, sulphur and nitrogen, in catchments of the drinking water reservoirs Josefův Důl and Souš. The mean annual fog drip from vegetation canopy was found between 88 and 106 mm (i.e. 7 to 9 percent of precipitation, and 11 to 13 percent of water yield, estimated by standard rain gauge monitoring). But, the mean annual load of sulphur and nitrogen by the fog drip was 1,975 and 1,080, kilograms per square kilometre, respectively (i.e. 55 and 48 percent of total deposition of sulphur and nitrogen, registered in the bulk. The acidification of surface waters leads to rising operational costs in the water treatment plants (liming, reduce of heavy metals, more frequent control of sand filters etc.). In a catchment scale, the additional precipitation, caused by the canopy fog drip, could be controlled by the effective watershed management (support of forests stands near the native composition with presence of deciduous trees: beech, mountain ash, or birch).